219k views
1 vote
Match the function with its graph.

1)y = tanx
2)y= cot x
3)y= -tan x
4)y= -cot x

Match the function with its graph. 1)y = tanx 2)y= cot x 3)y= -tan x 4)y= -cot x-example-1
Match the function with its graph. 1)y = tanx 2)y= cot x 3)y= -tan x 4)y= -cot x-example-1
Match the function with its graph. 1)y = tanx 2)y= cot x 3)y= -tan x 4)y= -cot x-example-2
Match the function with its graph. 1)y = tanx 2)y= cot x 3)y= -tan x 4)y= -cot x-example-3
Match the function with its graph. 1)y = tanx 2)y= cot x 3)y= -tan x 4)y= -cot x-example-4
User Fire Fist
by
5.8k points

2 Answers

2 votes

Answer:

A) 1C, 2A, 3B, 4D

Explanation:

We can graph each of the functions in your preferred grapher, the we compare each graph with the corresponding example. (attached images)

By doing this we can see that graph C is tanx, graph A is cotx, graph B is -tanx, graph D is -cotx

Match the function with its graph. 1)y = tanx 2)y= cot x 3)y= -tan x 4)y= -cot x-example-1
Match the function with its graph. 1)y = tanx 2)y= cot x 3)y= -tan x 4)y= -cot x-example-2
Match the function with its graph. 1)y = tanx 2)y= cot x 3)y= -tan x 4)y= -cot x-example-3
Match the function with its graph. 1)y = tanx 2)y= cot x 3)y= -tan x 4)y= -cot x-example-4
User Falieson
by
6.1k points
4 votes

Answer:

To quickly solve this problem, we can use a graphing tool or a calculator to plot each equation.

Please see the attached image below, to find more information about the graph

s

The equations are:

1) y = tan (x)

2) y = cot (x)

3) y = -tan (x)

4) y = -cot (x)

Looking at the graphs, we can see which corresponds to each equation

1) y = tan (x)

Graph C

2) y = cot (x)

Graph A

3) y = -tan (x)

Graph B

4) y = -cot (x)

Graph D

Match the function with its graph. 1)y = tanx 2)y= cot x 3)y= -tan x 4)y= -cot x-example-1
Match the function with its graph. 1)y = tanx 2)y= cot x 3)y= -tan x 4)y= -cot x-example-2
Match the function with its graph. 1)y = tanx 2)y= cot x 3)y= -tan x 4)y= -cot x-example-3
Match the function with its graph. 1)y = tanx 2)y= cot x 3)y= -tan x 4)y= -cot x-example-4
User Matthisk
by
5.7k points